Settlement Characteristics of Split Grouting Pile Composite Foundation in Loess Areas - Mingru Zhou; Lijun Xing; Yiming Chen; Hongxia Qiao (Advances in Civil Engineering)
Loess foundations often affect the stability of superstructures due to their insufficient bearing capacities; thus, reinforcement measures are crucial for mitigating the uneven settlement of foundations. This study aims to investigate the settlement characteristics of composite foundations for loess foundations reinforced by splitting grouting piles. First, split grouting tests were carried out on loess foundations. After the test piles reached the design strength, static load tests and geotechnical tests were carried out to obtain the Q-s curves of the test piles. The pile-forming mechanism was analyzed via excavations at an on-site test pile. Furthermore, the traditional settlement calculation method of composite foundations was used to calculate the settlement of split grouting pile composite foundations, and the results were compared with field test results to explore a suitable settlement calculation method of split grouting pile composite foundations. Finally, the numerical model of split grouting pile composite foundations was established according to the pile forming mechanism, and the settlement deformation characteristics of single pile and pile group composite foundations were analyzed. The relative errors of the composite modulus method and the stress correction method for calculating the settlement of the composite foundations were 6.4% and 32.8%, respectively, and the composite modulus method was closer to the test values. The calculated curves of the numerical model were in good agreement with the measured curves and relevant literature research results, demonstrating the rationality of the modeling method; the findings of this study provide theoretical guidance for designing loess foundation splitting grouting reinforcement and for predicting settlement during later construction periods.